Dissemination Of Realities: Need for Dispelling the Myths of Tetanus - Joshi, Mohan; Gumashta, Raghvendra; Kasturwar, NB; Deshpande, Amit (National Journal of Community Medicine, 2012)
Although the incidence of tetanus cases have decreased remarkably during last century, the authors have tried to analyze the WHO reports, government publication and other authentic sources, as derived mostly from Google Search Engine (with its inherent limitations of information availability, completeness and updating status) for finding out the prevailing root causes of myths and misconceptions related to tetanus. This study highlights only salient points of concern and underlines the need for qualitative epidemiological research for the benefit of public health planners, field level public health care functionaries, private health care providers and beneficiaries.